Anemia severa como factor de riesgo para parto pretérmino en gestantes atendidas en el Hospital Regional de Loreto 2021 a 2023 - Flores Urriola, Jerson Jairo (Universidad Nacional de la Amazonía Peruana, 2025)
A study will be conducted to demonstrate whether severe anemia is a risk factor for preterm birth in pregnant women treated at the Loreto Regional Hospital from 2021 to 2023. The study will be conducted using an analytical design, as it involves a comparison of study groups; an observational design, as no variables will be manipulated; a retrospective design, as it will involve a review of medical records; and a cohort design, as the study groups are organized according to the independent variable or risk exposure. For statistical analysis, the collected information will be tabulated and the results of the instruments used will be interpreted. Frequency distribution data will be obtained for qualitative variables; the chi-square statistical test will be used; significance will be considered if the chance factor is less than 5% (p < 0.05); the relative risk with its 95% confidence interval will be obtained, and multivariate analysis will be performed with logistic regression.

Se llevará a cabo un estudio para demostrar si la anemia severa es factor de riesgo para parto pretérmino en gestantes atendidas en el Hospital Regional de Loreto durante el periodo 2021 a 2023; por medio de un diseño analítico, porque implica comparación de grupo de estudio, observacional porque no se manipularan variables, retrospectivo porque serán con revisión de historias clínicas y de cohortes porque los grupo de estudio se organizan según la variable independiente o exposición de riesgo; para el análisis estadístico, se realizará la tabulación de la información recopilada y se interpretaran los resultados de los instrumentos utilizados. Se obtendrán datos de distribución de frecuencias para las variables cualitativas; se hará uso de la prueba estadístico chi cuadrado; considerando significancia si el azar es menor al 5% (p < 0.05); se obtendrá el riesgo relativo con su intervalo de confianza al 95% y el análisis multivariado con regresión logística.
Keywords: Trabajo de parto prematuro; Anemia; Factor de riesgo; https://purl.org/pe-repo/ocde/ford#3.02.02